Analysis of the Prognosis and Therapeutic Value of the CXC Chemokine Family in Head and Neck Squamous Cell Carcinoma - Li, Yongchao; Wu, Tinghui; Gong, Shujuan; Zhou, Hangzheng; Yu, Lufei; Liang, Meiyan; Shi, Ruijun; Wu, Zhenhui; Zhang, Jinpei; Li, Shuwei (Frontiers in Oncology, 2021)
Abstract The CXC chemokines belong to a family which includes 17 different CXC members. Accumulating evidence suggests that CXC chemokines regulate tumor cell proliferation, invasion, and metastasis in various types of cancers by influencing the tumor microenvironment. The different expression profiles and specific function of each CXC chemokine in head and neck squamous cell carcinoma (HNSCC) are not yet clarified. In our work, we analyzed the altered expression, interaction network, and clinical data of CXC chemokines in patients with HNSCC by using the following: the Oncomine dataset, cBioPortal, Metascape, String analysis, GEPIA, and the Kaplan–Meier plotter. The transcriptional level analysis suggested that the mRNA levels of CXCL1, CXCL2, CXCL3, CXCL5, CXCL6, CXCL8, CXCL9, CXCL10, CXCL11, and CXCL13 increased in HNSCC tissue samples when compared to the control tissue samples. The expression levels of CXCL9, CXCL10, CXCL11, CXCL12, and CXCL14 were associated with various tumor stages in HNSCC. Clinical data analysis showed that high transcription levels of CXCL1, CXCL2, CXCL5, CXCL10, CXCL12, and CXCL14 were linked with low relapse-free survival (RFS) in HNSCC patients. On the other hand, high CXCL6, CXCL11, and CXCL17 levels predicted high RFS outcomes in HNSCC patients. Meanwhile, increased gene transcription levels of CXCL3, CXCL7, and CXCL16 were associated with a higher overall survival (OS) advantage in HNSCC patients, while high levels of CXCL4, CXCL6, CXCL8, CXCL14, and CXCL17 were associated with poor OS in all HNSCC patients. This study implied that CXCL1, CXCL2, CXCL5, CXCL8, CXCL9, CXCL10, CXCL12, and CXCL14 could be used as diagnostic markers to identify low survival rate subgroups of patients with HNSCC as well as be potential suitable therapeutic targets for HNSCC patients. Additionally, CXCL3, CXCL6, CXCL7, CXCL11, CXCL16, and CXCL17 could be used as functional diagnostic biomarkers to identify better survival rate subgroups of patients with HNSCC.